Research on optimization technology of new pipeline design for regional natural gas pipeline network - Jingyi CUI; Kunfeng ZHU; Cuixian GAO; Li GU; Jing REN; Yuxing LI; Wuchang WANG (You-qi chuyun)
ObjectiveThe pipeline network has been continuously expanding to accommodate the increasing number of natural gas users and the rising gas consumption. However, the complex structure of the pipeline network, along with the diverse characteristics of gas supply and consumption, coupled with design parameters that influence one another, complicates the conventional planning and design of new pipelines. To meet future gas demand and enhance the efficiency of pipeline design, it is essential to review and analyze existing pipeline planning and design methods, as well as optimization algorithms. There is an urgent need to develop a set of design optimization methods suitable for complex pipeline network systems with multiple gas sources, numerous users, and aging pipeline infrastructures. MethodsFirstly, a three-level optimization approach was employed to create optimization models for natural gas pipeline network design under constraints such as hydraulic limitations along pipelines and energy consumption restrictions at compressor stations, with the goal of minimizing the present value of costs. The first-level model incorporates pipeline network layouts as decision-making variables for iterative solutions. The second-level model focuses on optimizing pipeline design capacities. The third-level model is responsible for design and optimization of pipeline diameters and compressor station parameters. Secondly, a particle swarm optimization algorithm was utilized for model solution optimization. Finally, the proposed methodology was applied to an actual natural gas pipeline network, from which the planning and design scheme was derived based on the calculations. ResultsIn comparison to the design that considered only the single condition of maximizing total transmission capacity, the design scheme for new pipelines derived from calculations based on various potential conditions for future pipeline networks proved to be more rational. The total cost of the optimal design scheme calculated using this optimization approach was 25.41％ lower than that of the traditional design scheme. ConclusionThe enhanced transportation capacity of the pipeline network demonstrates the effectiveness of the proposed planning model in minimizing the construction and operational costs of pipelines while meeting the transportation demands of the network.